Taxonomic study of the genus Blastobasis Zeller, 1855 (Lepidoptera: lastobasidae) from China, with descriptions of six new species - Teng, Kaijian; Wang, Shuxia (Zootaxa, 2019)
The ten species of the genus Blastobasis Zeller, 1855 recorded from Mainland China are reviewed, of which six are described as new: B. spinisetosa, sp. nov., B. divulgata, sp. nov., B. adamskii, sp. nov., B. aciformis, sp. nov., B. edentula, sp. nov., and B. hamata, sp. nov. Blastobasis parki Sinev, 1986 and B. inouei Moriuti, 1987 are recorded for the first time in China. Images of adults and genitalia are provided. A key to the species of Mainland China and a map showing their distributions are included.